Strengthening Mothers’ Community Engagement for Independent Learning in Dusun Kepetingan - Ika Ismawati; Yudy Prasetyo; Endah Alamsari Andayani (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
This community service program aims to strengthen mothers’ community engagement in fostering independent learning among children in Kepetingan Hamlet, Sawohan Village, Sidoarjo Regency. This article was written to find out how to implement community based strategies that empower mothers to actively participate in educational activities, as well as to describe the involvement of mothers' groups in supporting children's independent learning in Kepetingan Hamlet .Educational challenges in this area include limited parental involvement, low literacy and numeracy skills, and declining children’s motivation to learn, particularly due to geographical isolation and low educational backgrounds of parents. Recognizing mothers as primary caregivers and first educators at home, this program focused on empowering mothers to actively support their children’s learning processes. The program employed a Participatory Action Research (PAR) approach, involving mothers in all stages of the program, including problem identification, planning, implementation, reflection, and evaluation. Key activities included parenting education, literacy and numeracy training, science learning through simple experiments, and workshops on creating educational media using locally available and recycled materials. The results indicate a significant improvement in mothers’ confidence, knowledge, and participation in guiding children’s learning at home. Children also demonstrated increased motivation and engagement in independent learning activities. Furthermore, the establishment of a community-based learning forum (Sie Pendidikan) strengthened collaboration among mothers and ensured program sustainability. Overall, this program demonstrates that empowering mothers through community-based and participatory approaches can effectively cultivate a sustainable culture of independent learning at the family and community levels.